Influence of Rare Earth (Nd and Tb) Co‐Doping on ZnO Thin Films Properties. Issue 10 (25th October 2017) - El Fakir, Amina; Sekkati, Mouaad; Schmerber, Guy; Belayachi, Azzam; Edfouf, Zineb; Regragui, Mohammed; Cherkaoui El Moursli, Fouzia; Sekkat, Zouheir; Dinia, Aziz; Slaoui, Abdelilah; Abd‐Lefdil, Mohammed
Abstract : Zinc oxide thin films co‐doped with rare earth (Nd and Tb) have been grown on heated glass substrates (350 °C) by chemical spray pyrolysis method. The effect of doping rate on structural, optical, and electrical properties is studied. X‐ray diffraction confirmed that all the prepared films have the hexagonal wurtzite structure with a preferred orientation toward the c ‐axis. No peaks belonging to rare earth or their oxides are observed in the limit of XRD technique detection. UV–visible‐NIR spectra show a significant optical transmission above 75%, which decrease with the increase of Tb concentration and an increase of the optical band gap with the insertion of the rare earth dopants. Photoluminescence spectra are dominated by an emission band attributed to the radiative recombination of excitons and a large band attributed to the various defects in ZnO matrix. In addition band emissions from Nd3+ ions are observed in the (Nd, Tb) co‐doped films. Electrical resistivity of about 3.7 10–2 Ω · cm was achieved. Abstract : We report the deposition of Zinc oxide thin film co‐doped with rare earth (Nd and Tb) by spray pyrolysis technique. The thin films exhibit good optical and electrical properties. Photoluminescence spectra of the deposited samples show a specific broad band emissions due to the 4f electron transition of the Nd 3+ ions in the (Nd, Tb) co‐doped films.